Investigation of the dielectric properties and mechanical stability of lignocellulosic biomass based electrical insulation material for high voltage applications - T Rajamanikandan; S Banumathi; B Karthikeyan (Materials Research Express, 2023)
The laminated insulation pressboards are used in electrical transformers and they are made from pure wood cellulose fibre. It is used in high-voltage transformers for electrical insulation due to its superior electrical and mechanical properties. Many researchers are searching for alternatives to wood raw materials to reduce deforestation. The banana is one of the lignocellulose-based raw materials; the banana fibre contains 48% cellulose. In this work, different frequencies and temperatures are used to investigate the electrical characteristics of epoxy resin composites reinforced with banana leaf fibres, including their dielectric constant, dissipation factor, and loss factor. At frequencies ranging from 1 to 10 kHz and temperatures ranging from 30 to 150 °C, the dielectric properties of several composites containing banana leaf fibre are studied. The composite’s dielectric properties gradually increased with temperature and decreased with frequency. Correspondingly, the mechanical tests involving a banana leaf fibre epoxy composite are conducted for tensile, bending, impact, and water absorption. The banana leaf fibre has been treated with a 5% sodium hydroxide (NaOH) solution to increase its dielectric and mechanical strength. According to this study, the mechanical strength of biocomposites containing up to 60% treated banana leaf fibre epoxy (TBLFE) composites is greater than that of pure epoxy. A thermogravimetric investigation of composites reinforced with banana fibres has revealed remarkable thermal stability up to 220 °C. In a composite made from chemically treated banana fibre pressboard, there is a good bond between the fibres and the matrix. The FESEM surface analysis shows that treated banana leaf fibril insulation boards have a better texture than composites that have not been treated. The testing results depict that banana leaf fibre is one of the good alternatives to wood cellulose for electrical insulation on pressboard for high-voltage applications.